Des livres pour « faire joli » ? - Marine Le Bail (Contextes)
Can books be treated as mere decorative items ? From the 19th Century, when books started to beceome everyday consomer products, to nowadays, when social media tend to promote books by associating them with vintage and comforting values, books have found their place in the field of decorative arts and have been present in interior decoration manuals. Indeed, books can be at the center of several scenographies that contribute to expose them at home ; as such, they become part of our daily environment. Beyond their aesthetic interest, however, books are also part of a self-dramaturgy that takes place at home as well on the Bookoverse, according to new patterns. Nevertheless, the decorative uses of books tend to conflict with the dominant axiology that subordinate books to reading. Contrary to the temptation of opposing reading and non-reading as to celebrate the first one and condamn the latest, this paper aims at showing that decorative uses of books can be seen as a prolongation of our relation towards texts by making them immediately visible in our day-to-day environment.